AN ETHNOPRAGMATICS STUDY OF APOLOGIZE SPEECH ACTS IN JAVANESE (KAJIAN ETNOPRAGMATIK TINDAK TUTUR MEMINTA MAAF DALAM BAHASA JAWA ) - Endang Sri Maruti; Teguh V Suharto; Nur Samsiyah (Jurnal Gramatika, 2021)
Apologies are usually made by someone if they make a mistake. However, apologies for the speech community in Java are not only done after the speaker has made a mistake for a speech or action taken to the speaker, sometimes before doing or telling something that is considered wrong or taboo. In the Javanese speaking community, apologizing tends to be stated in advance even though what is actually said or done is not necessarily wrong. The focus of this research is the speech act form apologizing to the Javanese community in the area of Beringin Village, Lakarsantri District, Surabaya City. This study has a qualitative descriptive approach with an ethnopragmatic design. Research data in the form of situations, events, and communicative actions containing apologies obtained from 46 research subjects through observation and in-depth interviews. The data analysis method is the equivalent and split method with techniques for direct elements, such as missing techniques, dressing techniques, and expansion techniques. The results of this study: (1) the form of speech to apologize is different in modes and components; (2) The form of apologizing is componentially an open form, but in expression, in the same sentence, components that indicate the level of sincerity or other purposes are also inserted other than for the purpose of apologizing.